A Brief Overview on Autosomal Trisomies - Priyanka Pandey; Rakesh Kumar Verma (Recent Developments in Medicine and Medical Research Vol. 15, 2021)
Trisomy refers to the presence of an additional chromosome to the normal diploid number. It is the most common abnormality of the chromosome number. The usual cause of this numerical error is meiotic non – disjunction of chromosomes, resulting in a gamete with 24 instead of 23 chromosomes and subsequently in a zygote with 47 chromosomes. Trisomy of autosomes is associated with three main syndromes: Trisomy 21 or Down’s syndrome, Trisomy 18 or Edward Syndrome, Trisomy 13 or Patau Syndrome. Other rare trisomies include trisomy 8, trisomy 9, trisomy 2. Trisomy 21 constitutes the most common chromosomal abnormality among live births (1 in 730 live births) and the most frequent form of intellectual disability caused by microscopically demonstrable chromosomal aberrations Genetic cause for this syndrome is trisomy of chromosome 21 or the presence of distal part of the long arm of chromosome 21. The cytogenetic profile of down syndrome includes free trisomy 21, Robertsonian translocations, mosaicism, duplication of the DS critical region and other structural rearrangements involving chromosome 21. Edward syndrome is the second most common autosomal trisomy observed in live births with its prevalence ranging from 1/3600 to 1/10,000 with the best overall estimate in liveborns as 1 in 6,000. The trisomy 18 (Edwards syndrome) phenotype results from full, mosaic, or partial trisomy 18q . Complete or full trisomy 18 is the most common form (about 94% of cases); in this situation every cell contains three entire copies of chromosome 18. Trisomy 13 (Patau Syndrome) constitutes the third most common autosomal trisomy in live births. Its incidence is 1 in 12000 live births as with other trisomy disorders, there are three types of Patau syndrome: Full trisomy 13 which is the most common type. People with this type have three full copies of chromosome 13. Partial trisomy 13 in which people have two full copies of chromosome 13 and an extra part of chromosome 13. Mosaic trisomy 13 where some of the body’s cells have three copies of chromosome 13 whereas others have two normal copies. We aim to provide an overview of above mentioned autosomal trisomy disorders in respect of their incidence, chromosomal aberrations clinical features, and management.